Konstruksi Kritik Tokoh Publik dalam Media Online: Analisis Wacana Kritis Teun A. Van Dijk Terhadap Berita Mens Rea Pandji Pragiwaksono di Kompas.com - Wardoyo Dingkol (UIN Raden Mas Said Surakarta, 2025)
This study aims to describe the construction of critical discourse targeting public figures in online media through a critical discourse analysis based on Teun A. Van Dijk’s model, applied to the article titled “Pandji Pragiwaksono’s Series of Criticisms in the Special Show Mens Rea” on kompas.com, using a qualitative descriptive research method. The results of the study indicate that kompas.com systematically constructs Pandji’s criticism as a significant cultural phenomenon by blending elements of commercial entertainment with post-2024 Presidential Election civic unease. Kompas.com positions itself as a mediator for crucial issues such as the democratic crisis, dynastic politics, the weakening of the opposition, and legal skepticism by employing a thematic classification scheme and word choices that maintain journalistic objectivity while remaining rhetorically sharp. The discourse constructed by Kompas.com is not merely entertainment, but a political document that performs a social control function by facilitating criticism of those in power amidst the limitations of formal opposition spaces. This study contributes to broadening public perspectives by comparing media frames with differing ideological tendencies in responding to criticism of public figures, thereby mapping discourse polarization more comprehensively.